2006
DOI: 10.1186/1472-6963-6-126
|View full text |Cite
|
Sign up to set email alerts
|

Internal medicine specialists' attitudes towards working part-time: a comparison between 1996 and 2004

Abstract: Background: Although medical specialists traditionally hold negative views towards working parttime, the practice of medicine has evolved. Given the trend towards more part-time work and that there is no evidence that it compromises the quality of care, attitudes towards part-time work may have changed as well in recent years. The aim of this paper was to examine the possible changes in attitudes towards part-time work among specialists in internal medicine between 1996 and 2004. Moreover, we wanted to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…If living with a partner is as important for men as it is for women the coming generation of doctors will be more open-minded and support a cultural change in which surgery specialties are more accessible to women. Not all medical specialties facilitate the balance between home and work [1,36]. This situation may limit students with a partner in their choices, raising the possibility that they reconsider their initial choice and opt for a medical specialty more appropriate to their circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If living with a partner is as important for men as it is for women the coming generation of doctors will be more open-minded and support a cultural change in which surgery specialties are more accessible to women. Not all medical specialties facilitate the balance between home and work [1,36]. This situation may limit students with a partner in their choices, raising the possibility that they reconsider their initial choice and opt for a medical specialty more appropriate to their circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should at least include students who are in specialist training, because the number of students living with a partner is rather small in this study [36,40]. …”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] As documented in other specialties, most departments of obstetrics and gynecology have part-time faculty. [11][12][13][14][15][16] It is not surprising that the chairs anticipate an increase in requests for part-time positions by future faculty. A recent study demonstrated an increase of part-time faculty in internal medicine by 88% in the past 20 years.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing research is being performed on the effects of physicians working parttime in healthcare [4][5][6][7][8][9][10][11][12]. Several of these studies reported no differences between parttime and fulltime physicians in terms of (quality) performance [11,12].…”
Section: Introductionmentioning
confidence: 99%